Subjetividades e trabalho na polícia civil - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The general objective of this study is to understand how the subjectivities of civil servants of a Civil Police Station in the State of Rio Grande do Sul are constituted based on their work relationships. To this end, the research was exploratory, with a qualitative approach based on the cartographic method. Data production was carried out through participant observation, documentary research and interviews, the latter being conducted with seven Civil Police Officers. The narrative technique was adopted for data analysis. The results indicate that the subjectivity of these civil servants permeates several work issues, such as: the fact that these professionals do not have training updates, the lack of institutional psychological support and the ambiguous criticism of society. However, these civil servants relate the nature of police work as something noble, dignified and differentiated, since it involves serious issues such as the life and safety of the entire civilian population. Thus, the subjectivity of the Police Officers is constituted in a conflict that, on the one hand, involves the devaluation of society when their expectations are not met and the appreciation when these are met; and on the other, the frustration arising from this ambiguous recognition of society contrasted with the support and internal recognition by colleagues. This means that the subjectivity of these Police Officers is never in its full form, constantly oscillating between impasses generated by work dynamics.
Subjectivities and work in the civil police
Keywords: Relações de trabalho; Trabalho policial; Produção de subjetividade; Polícia civil; Production of subjectivity; Police work; Labor relations; Civil police; CNPQ::CIENCIAS SOCIAIS APLICADAS